Application of equity sensitivity theory to problem-solving approaches in construction dispute negotiation - Yiu TW; Keung CW; Wong KL (Massey University)
This study applies equity sensitivity theory to investigate how the sensitivity of negotiators to perceived equity or inequity varies with their perception of the adoption of problem-solving approaches (PSAs) in negotiation in the construction industry. Drawing upon this theory, we identify three classes of negotiators: benevolents (known as "givers"), equity sensitives, and entitleds (known as "takers"). Our results suggest that most of the negotiators in our sample are entitleds. The study also provides statistical evidence that the perception of the adoption of PSAs appears to be associated with the degree of equity sensitivity of negotiators. For instance, benevolents demonstrate a significantly stronger preference for the adoption of PSAs and are thus able to obtain a higher level of negotiation satisfaction compared to the other types of negotiators. These findings are particularly relevant to the corporate managers of construction organizations, who may want to consider the inherent equity sensitivity traits of their negotiators before sending them to the negotiating table. © 2011 ASCE.
This material may be downloaded for personal use only. Any other use requires prior permission of the American Society of Civil Engineers. This material may be found at https://ascelibrary.org/doi/10.1061/%28ASCE%29ME.1943-5479.0000031
Keywords: Negotiation; Equity sensitivity; Problem-solving approach; Disputes; 0904 Chemical Engineering; 1202 Building; 1503 Business and Management